Optimalisasi Pemanfaatan Lahan Pekarangan Melalui Usahatani Sayuran di Desa Babadsari Kecamatan Kutowinangun Kabupaten Kebumen - Arif Pramudibyo; Zulfanita Zulfanita; Dyah Panuntun Utami (Surya Agritama: Jurnal Ilmu Pertanian dan Peternakan, 2022)
This study aims to determine: (1) the pattern of farming yard (2) the cost, revenue, profitability and feasibility of each commodity vegetable farming, (3) the feasibility of each commodity, (4) comparison of the feasibility of each commodity vegetables to household incomes of farmers, (5) contribution to total revenues of all vegetable crops against household income of farmers. The method used in this research is a survey. The study population was 76 farmers, and a sample of 43 farmers was taken with an error rate of 10%. Sampling using proportional random sampling method. Data analysis used descriptive analysis, farming analysis, farming feasibility, and contribution. The results of the analysis show that: (1) The cropping pattern used is crop rotation, (2) The costs incurred for cultivating pulled spinach Rp. 1,034,073.66, income Rp. 7,471,120, 97 and profit Rp. 6,934,693.78. Costs incurred for green mustard cultivation amounted to Rp. 1,041,226.26, income Rp. 6,598,702.20 and profit Rp. 6,042,122.58. Costs incurred for cultivating kale Rp. 958,295.61; income Rp. 4,001,934.82 and profit Rp. 3,468,797.41, (3) Farming all types of vegetables in the yard in Babadsari Village is feasible to cultivate, (4) The contribution value obtained from the cultivation of spinach is 93.62%, the contribution value obtained from cultivation green mustard is 82.69%, while the contribution value obtained from kale cultivation is 50.20% and (5) The contribution value obtained by Babadasari Village farmers from yard land cultivation is 56.70%, so the contribution of home garden farming is categorized as high. Keywords: optimization, contribution, land yard, farm vegetables